2020
DOI: 10.1038/s41467-020-17318-x
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of antibodies against SARS-CoV-2 among health care workers in a large Spanish reference hospital

Abstract: Health care workers (HCW) are a high-risk population to acquire SARS-CoV-2 infection from patients or other fellow HCW. This study aims at estimating the seroprevalence against SARS-CoV-2 in a random sample of HCW from a large hospital in Spain. Of the 578 participants recruited from 28 March to 9 April 2020, 54 (9.3%, 95% CI: 7.1–12.0) were seropositive for IgM and/or IgG and/or IgA against SARS-CoV-2. The cumulative prevalence of SARS-CoV-2 infection (presence of antibodies or past or current positive rRT-PC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

55
360
16
21

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 376 publications
(452 citation statements)
references
References 35 publications
55
360
16
21
Order By: Relevance
“…[23] In a tertiary hospital in Barcelona, 45 (9.3%) out of 578 HCW were seropositive for antibody against SARS-CoV-2. [24] We postulate the discrepancy between our study and others could be multifactorial. First of all, Malaysia had a relatively low COVID-19 incidence compared to these countries during the study period.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…[23] In a tertiary hospital in Barcelona, 45 (9.3%) out of 578 HCW were seropositive for antibody against SARS-CoV-2. [24] We postulate the discrepancy between our study and others could be multifactorial. First of all, Malaysia had a relatively low COVID-19 incidence compared to these countries during the study period.…”
Section: Discussioncontrasting
confidence: 78%
“…[33][34][35][36] A study from Spain in March 2020 observed no difference in the COVID-19 infection rate of HCW by professional categories and risk of exposure in respective work departments. Other studies in Spain [24] , Italy [23] and Netherlands [37] also suggested the risk to a HCW of contracting COVID-19 infection in a healthcare facility is minimal. Although our study was unable to fully rule out additional risks of COVID-19 infection in a healthcare facility, zero seroprevalence of anti-SARS-CoV-2 antibody among asymptomatic HCW should reassure the public that the risk of being infected by a HCW is very low.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…To the best of our knowledge, no studies gather such a population without discriminating by other factors. Therefore, the features included in our cohort are not dissected in population-based wide studies such as those performed in Spain 11 or Switzerland 16 , nor in published studies addressing the seroprevalence against SARS-CoV-2 speci cally in HCWs 12,13,[17][18][19][20] .…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, our data confers to HCWs an IgG seroprevalence of 25.58% (95% IC: 13.52 -41.17). Other studies focused in these professionals reveals rates ranging from 2% 18 , 7.5% 17,20 , 10% [11][12][13] to nearly 20% 19,21 . Our results are in the upper range and backed by recent data from a large cohort of HCWs in a secondary teaching hospital in Madrid province 22 .…”
Section: Discussionmentioning
confidence: 99%